2023
DOI: 10.1007/s40864-022-00184-9
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Metro Choice Behaviour of Suburban Rail Passengers in India

Abstract: This study aims to analyse the inter-rail modal shift behaviour of suburban rail passengers to examine ridership for the proposed metro extension corridor in Chennai, India. This investigation was conducted in 2019 as part of a feasibility study for the extension of the metro line spanning between Chennai Airport and Kilambakkam, a southern suburb of Chennai. The same origin–destination pair is also served by the suburban rail system. It is an extension of the operating line from Washermenpet to the airport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…This paper presents an operational strategy for optimizing both full-length and shortturn routes using virtual coupling technology. We have developed an integrated optimization model that minimizes passenger travel time and operational costs, taking into account the variability in passenger flow [37][38][39][40]. This model includes constraints related to station services, train operations, virtual coupling, rolling stock circulation, and passenger ride selection.…”
Section: Discussionmentioning
confidence: 99%
“…This paper presents an operational strategy for optimizing both full-length and shortturn routes using virtual coupling technology. We have developed an integrated optimization model that minimizes passenger travel time and operational costs, taking into account the variability in passenger flow [37][38][39][40]. This model includes constraints related to station services, train operations, virtual coupling, rolling stock circulation, and passenger ride selection.…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that fare difference, age, and wealth have a significant impact on shift behavior. Selvakumar et al [11] investigated the ridership of the proposed metro extension corridor in Chennai, India, by analyzing the inter-rail modal shift behavior of suburban train passengers. Using a stated preference questionnaire, a sample of 272 suburban rail customers traveling for employment, school, and other purposes was questioned for this inter-rail competition study.…”
Section: Studies On Mode Shift To Metromentioning
confidence: 99%
“…Several studies were conducted on the modal shift in behavior in response to the new MRT [1,[8][9][10][11][12]. This study, for the first time, applies behavioral theories to explore the factors affecting commuters' choice towards the MRT over the existing mode of transport.…”
Section: Introductionmentioning
confidence: 99%